2019
DOI: 10.1111/jnu.12516
|View full text |Cite
|
Sign up to set email alerts
|

Relational‐Level Factors Influencing Suicidal Behaviors Among Korean Adolescents

Abstract: Purpose To identify relational‐level risk and protective factors for suicidal ideation, suicide plan, and suicide attempt in a nationally representative sample of Korean adolescents. Study Design This study is a secondary data analysis of cross‐sectional national data on Youth Health Behavior collected in June 2017. The final sample (n = 62,276), collected from 2,400 classes in 800 schools, reflects stratification, clustering, and weight. It is representative of the population (n = 3,027,488). Methods This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…However, the results of previous studies are inconsistent. Some showed a lower age in the suicide group than the non-suicide group, while others showed that the incidence of SRB increased with age, which may be due to the different inclusion criteria used for the samples (62,63). This difference may also be related to the different grouping methods used in each study.…”
Section: Discussionmentioning
confidence: 97%
“…However, the results of previous studies are inconsistent. Some showed a lower age in the suicide group than the non-suicide group, while others showed that the incidence of SRB increased with age, which may be due to the different inclusion criteria used for the samples (62,63). This difference may also be related to the different grouping methods used in each study.…”
Section: Discussionmentioning
confidence: 97%
“…One possible explanation is that these groups could differ in the type of relationships with con dants (e.g., parents, family members, peers). From early to middle adolescence, the proportion of those who prefer parents over others as primary con dants is reported to decrease (44), and research has also indicated that adolescents who do not report parents as con dants have worse mental health (15,45,46). Future studies should explore the effects and take into account the nature of con dant relationships.…”
Section: Discussionmentioning
confidence: 99%